The Impact of Maternal Anaemia on Foetal Growth Parameters in Somali Women: A Cross-Sectional Study - Erkok, Umut; Topçu, Güneş; Yıldız, Pınar; Güner, Gazi; Hassan, Ifrah Salad; Gök, Koray; Barut, Adil (Cerrahpaşa Medical Journal, 2025)
Objective: Anemia is a magnitude of public health problem globally, mainly affecting pregnant women, particularly in underdeveloped countries like Somalia. This study aimed to address this gap by determining the prevalence of maternal anemia and its association with birth weight outcomes in Somalia. Methods: This cross-sectional study was conducted at the Mogadishu Somali Turkey Training and Research Hospital between April 1 and September 25, 2023, involving 808 consecutive mothers who delivered in the third trimester. Maternal hemoglobin levels were measured at the time of delivery, and fetal growth parameters, including birth weight, height, head circumference, and APGAR score, were assessed. Results: The study found that 67% of pregnant women had anemia. The majority of anemic patients (41.5%) had moderate anemia. In regression analysis, maternal hemoglobin level (P = .0001) and severe anemia (OR=3.28, 95%CI:1.54-6.95, P = .002) were independent risk factors for low birth weight (LBW). Also, maternal hemoglobin (P = .012) and severe anemia (OR=3.57, 95%CI:1.61-7.91, P = .002) were independent risk factors for a birth weight of ≥1500–2499 g. Conclusion: The prevalence of anemia in pregnancy in Somalia is alarmingly high, with 67% of women affected. This study demonstrates a strong association between maternal anemia, particularly severe anemia, and adverse fetal growth outcomes, including LBW. These findings highlight the urgent need to address maternal iron requirements through targeted nutritional interventions, including iron supplementation and dietary support during pregnancy. Improving maternal nutrition and healthcare access is essential to enhancing fetal health and reducing the incidence of LBW in Somalia. Cite this article as: Erkok U, Topçu G, Yıldız P, et al. The impact of maternal anemia on fetal growth. Cerrahpaşa Med J. 2025, 49, 0019, doi:10.5152/cjm.2025.25019.